Linkages between policy and business innovation in the development of China's energy performance contracting market. (May 2020) - Zhou, Yuanrong; Evans, Meredydd; Yu, Sha; Sun, Xiaoliang; Wang, Juemin
Abstract: China has a large and growing energy performance contracting (EPC) market. In 2017, the EPC investment was 111 billion CNY, making China the largest EPC market globally. EPC has played a significant role in driving energy efficiency improvement. This paper evaluates four key factors driving the EPC market and their interactions: incentive policies, China's Five-Year Plans, and business innovations in diversifying contract models and strengthening measurement and verification (M&V). We use multiple data sources: detailed information from 21 pilot projects, industry-wide surveys, and policy information. Our study indicates that supportive policies were important for the initial market development; after introducing government incentives in 2010, ESCO employees doubled within a year and the annual total energy savings from EPC projects increased from 11 million tce in 2010 to 34 million tce in 2015. As the market was established and continued to grow, the private sector undertook the initiative to address the issues that were left out of policies. By diversifying contract models and taking robust M&V practices, EPC stakeholders were able to overcome certain market barriers and enabled the sustainable growth of the market. Future EPC policies could incorporate business innovations to ensure long-term development of China's EPC market. Highlights: The interplay between policies and business innovations is crucial for China's EPC market development. Supportive policies were important for the initial market development. Business innovations, by filling policy vacuum, ensured the market's sustainable development.